2021
DOI: 10.3389/feart.2021.773088
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Flexural Toppling Failure in Rock Slopes Using Discrete Element Method

Abstract: Flexural toppling failure is a common failure mode of natural and artificial rock slopes, which has caused serious damage to human life and property. In this work, an advanced numerical method called the Universal Distinct Element Code (UDEC) was used to study the mechanism of flexural toppling failure. In total, more than twenty slope models were built and analyzed. Two new parameters (displacement discontinuity and transition coefficient of failure surface) were introduced to present a further understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…For other coseismic landslides in Torlesse graywacke rock mass triggered by the Kaikōura earthquake, Singeisen et al (2022) identified that the geometry of failures cannot be explained by the identified joint sets of meter-scale persistence alone but is consistent with sliding along centimeter-to decimeter-scale discontinuities in the highly jointed rock mass. While flexural toppling can result in sliding (Adhikary et al, 1997;Hungr et al, 2014;Zheng et al, 2021), brittle failure of intact rock is not required at Half Moon Bay due to the closely fractured nature of the Torlesse graywacke rock mass. Instead, ridge renting and flexural toppling in this case are likely to contribute to slope destabilization through the opening of joints and fractures, which in turn leads to decreasing rock mass interlocking and allows for failure to occur more easily along centimeter-to decimeter-scale discontinuities (i.e., what we refer herein as joint-step-path failure; Singeisen et al, 2022).…”
Section: Structural Evidencementioning
confidence: 99%
“…For other coseismic landslides in Torlesse graywacke rock mass triggered by the Kaikōura earthquake, Singeisen et al (2022) identified that the geometry of failures cannot be explained by the identified joint sets of meter-scale persistence alone but is consistent with sliding along centimeter-to decimeter-scale discontinuities in the highly jointed rock mass. While flexural toppling can result in sliding (Adhikary et al, 1997;Hungr et al, 2014;Zheng et al, 2021), brittle failure of intact rock is not required at Half Moon Bay due to the closely fractured nature of the Torlesse graywacke rock mass. Instead, ridge renting and flexural toppling in this case are likely to contribute to slope destabilization through the opening of joints and fractures, which in turn leads to decreasing rock mass interlocking and allows for failure to occur more easily along centimeter-to decimeter-scale discontinuities (i.e., what we refer herein as joint-step-path failure; Singeisen et al, 2022).…”
Section: Structural Evidencementioning
confidence: 99%
“…Moreover, data of various aspects can be monitored in real time during the entire deformation and destabilisation process Ning et al 2021;Xie et al 2023). Studies indicated that lithology significantly influences the deformation and destabilisation modes of anti-dip rock slopes, and the thickness and dip angle of the rock strata as well as the slope angle significantly influence the stability coefficient (Zheng et al 2021;Dong et al 2020;Xie et al 2023). Zhang et al (Zhang et al 2022) applied UDEC to study the influence of the geometric and mechanical characteristics of joints on the location of the failure surface and stability coefficient of anti-dip rock slopes.…”
Section: Introductionmentioning
confidence: 99%